Measuring and analyzing the impact of public spending on unemployment rates in Iraq for the period (2004 - 2024) - Abdullah, Asst.L. Chryan Hadi (Sulaimani Journal for Humanities, 2026)
Unemployment is a widespread economic and social problem that many countries face, and they attempt to address it using various economic tools. Public spending is one such tool that some countries and governments resort to in order to reduce unemployment rates, due to a range of economic, financial, and social factors. This approach can, however, produce economic, financial, and social consequences. This research aims to measure and analyze the impact of public spending on unemployment rates in Iraq during the period 2004-2024. It employs a descriptive methodology using tables, percentages, and related data, in addition to using the standard method of the ARDL model through time series data analysis. The research concludes that there are positive effects of public spending on unemployment rates, as well as positive effects of exchange rate fluctuations and investment on unemployment. It also finds negative effects of the ISIS war and unemployment. Therefore, countries and governments should reconsider the issue of public spending in terms of its causes, allocation methods, and its connection to strategic investment projects, which can be a suitable tool for reducing unemployment rates.
Keywords: Public spending; unemployment rates; exchange rate